Practical Guidance of the GTH Haemophilia Board on the Use of Emicizumab in Patients with Haemophilia A - Holstein, Katharina; Albisetti, Manuela; Bidlingmaier, Christoph; Halimeh, Susan; Heine, Sabine; Klamroth, Robert; Königs, Christoph; Kurnik, Karin; Male, Christoph; Oldenburg, Johannes; Streif, Werner; Wermes, Cornelia; Escuriola-Ettingshausen, Carmen; on behalf of the ‘Ständige Kommission Hämophilie’ (Haemophilia board) of the German, Swiss Austrian Society for Thrombosis Haemostasis Research (GTH) (Hämostaseologie, 2020)
Emicizumab has been approved for bleeding prophylaxis in patients with haemophilia A (PWHAs) with or without inhibitors. Because of substantial differences between factor VIII (FVIII) and Emicizumab, the ‘Ständige Kommission Hämophilie’ of the German, Austrian, Swiss Society for Thrombosis and Haemostasis Research (GTH) established a practical guidance for the use of Emicizumab in PWHAs. A systematic literature research was conducted in PubMed. Based on this and on personal experience, this practical guidance has been developed. Each single statement has been discussed among members of the ‘Ständige Kommission Hämophilie’ and revised accordingly. The final set of recommendations has been approved by all authors analogous to the Delphi method. This practical guidance is provided for physicians treating PWHAs with regard to general aspects, patient education, bleeding treatment, surgery, use of Emicizumab in previously untreated patients (PUPs), patients with newly diagnosed inhibitors and elderly patients. Patients should be treated in expert centres and adequate laboratory tests to monitor Emicizumab levels, FVIII replacement and inhibitors should be available. Early experience of immune tolerance induction protocols integrating Emicizumab is reviewed, and the limited experience in PUPs and very young children is described. So far, no thromboembolic complications have been reported with the concomitant use of FVIII or recombinant activated FVII for bleeding treatment or surgery. Activated prothrombin complex concentrate doses of >100 U/kg for >24 hours should be avoided whenever possible because of the high risk of thrombosis and/or thrombotic microangiopathy. In conclusion, this study is designed to support haemophilia physicians using Emicizumab in physicians treating hemophilia and using (PWHAs). With further post-marketing experience and trials, regular updates are necessary.
Keywords: Emicizumab; haemophilia A; inhibitors; prophylaxis